PENGARUH PENGAWASAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI INSPEKTORAT KABUPATEN TASIKMALAYA - Setia Rachmanda, Yudi; Febiyani Lestari, Dheri (LP2M Universitas Perjuangan Tasikmalaya, 2023)
The aims of this research are: 1). To find out about the supervisory measures implemented by the Tasikmalaya Regency Inspectorate. 2). To find out the motivation of Tasikmalaya Regency Inspectorate employees. 3). To find out the performance of Tasikmalaya Regency Inspectorate employees. 4). To determine the effect of supervision and motivation on the performance of Tasikmalaya Regency Inspectorate employees. The research method used is descriptive and verification methods. Data collection techniques were carried out through field research and literature study. The data analysis technique is carried out through Correlation Coefficient analysis to find the